Historical series of cases of COVID-19 in brazilian regions in the year of 2020 - Gouveia, Guilherme Pertinni de Morais; Gouveia, Samara Sousa Vasconcelos; Vasconcelos, Samila Sousa; Silva, Elisson de Sousa Mesquita; Medeiros, Rebeca Galdino; da Silva, Rosangela Lago (Journal of Health & Biological Sciences, 2020)
Aim: To analyze the incidence and lethality of COVID-19 in Brazil, through a historical series. Methods: Retrospective ecological study carried out by analyzing biweekly time series with secondary data from Brazilian regions and states, was on the state and integral health sites of the State of Health and IntegraSUS, related to SARS-CoV disease, from March to May 2020. Results: All states showed an increasing incidence trend, except Ceará. The highest lethality found was from Piauí. However, in the last analyzed period, the states of Rio de Janeiro, Pernambuco, São Paulo and Ceará stood out. The North had an increased incidence in relation to the others and the Southeast had the highest lethality rate. Conclusion: There was an increasing trend in incidence in all states, except Ceará. Piauí had the highest lethality coefficient. Considering the regions, the North showed an increasing trend in incidence and lethality was higher in the Southeast.